Arsenic removal from water by nanofiltration membrane: potentials and limitations - Chabi Noël Worou (IWA Publishing, 2021)
Arsenic, in addition to being a confirmed carcinogen, is one of the most toxic elements found in nature, and should therefore be removed if the concentration is greater than 10 μg/L. Nanofiltration (NF) membranes have succeeded in arsenate As (V) ions removal from water almost completely. It is reported in this review that, like reverse osmosis (RO) membranes, NF membranes have not yet performed alone arsenite As (III) ion rejection without being associated with another technology. Commercial NF membranes exhibited a rejection between 86 and 99% towards arsenate As (V) while As (V) removal reached 99.8% for synthesized NF membranes. Since commercial NF membranes have shown their limit, scientists have prepared novel NF membranes that demonstrated long-term efficiency, fouling reduction, cost reduction, an increase in separation of multivalent ions, rejection performance, or a high flux achievement, depending on the area of use. For small treatment plants, NF is a more cost-effective method. The review succinctly reported arsenic as a serious global contamination issue and focused on novel nanofiltration processes for arsenic rejection to safeguard water security. This article also developed a comparative study of nanofiltration and reverse osmosis techniques concerning arsenic removal. Finally, future trends and perspectives have been highlighted with particular emphasis on emerging synthesis techniques of NF membranes without hiding the unpleasant fouling issue that limits its competitiveness. Highlights Commercial nanofiltration (NF) membranes for arsenic removal.; Novel synthesized nanofiltration membranes.; Potential and limitation of nanofiltration membranes in arsenic removal.; Influence of operating parameters on arsenic removal.; Performance comparison of reverse osmosis (RO) and nanofiltration (NF) membranes in the context of arsenic removal.;